Penggunaan teknologi dalam pengajaran Bahasa Arab - Iffatunnisa, Fathina (Maliki Interdisciplinary Journal, 2024)
The use of technology in the educational context has experienced rapid development in the last few decades. One area affected by this change is Arabic language teaching. This article examines the use of technology in teaching Arabic, explores various related aspects, and provides insight into how technology has influenced the way Arabic is taught and learned.